2021
DOI: 10.3389/fbioe.2020.558771
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Movement Smoothness From Inertial Measurement Units

Abstract: Inertial measurement units (IMUs) are increasingly used to estimate movement quality and quantity to the infer the nature of motor behavior. The current literature contains several attempts to estimate movement smoothness using data from IMUs, many of which assume that the translational and rotational kinematics measured by IMUs can be directly used with the smoothness measures spectral arc length (SPARC) and log dimensionless jerk (LDLJ-V). However, there has been no investigation of the validity of these app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…need to be considered. For instance, recent work on estimating movement smoothness with IMUs has shown that the SPARC measure cannot be used with acceleration data, even though the SPARC has been shown to be a good measure of movement smoothness when applied on movement velocity (Melendez-Calderon et al, 2021).…”
Section: Movement Quality (Mq)mentioning
confidence: 99%
“…need to be considered. For instance, recent work on estimating movement smoothness with IMUs has shown that the SPARC measure cannot be used with acceleration data, even though the SPARC has been shown to be a good measure of movement smoothness when applied on movement velocity (Melendez-Calderon et al, 2021).…”
Section: Movement Quality (Mq)mentioning
confidence: 99%
“…However, as an IMU measures accelerations, estimating velocity from it would require additional processing and is usually prone to drift (Woodman, 2007). In a recent study, Melendez-Calderon and colleagues suggest that SPARC should not be applied to linear velocities obtained from IMUs, and an alternative definition based on angular velocities may be of interest (Melendez-Calderon et al, 2021). However, techniques to correct drift due to strapdown integration (Woodman, 2007) were not employed in their study, as the authors suggest that it warrants a systematic analysis of the errors introduced in the smoothness estimate (Melendez-Calderon et al, 2021).…”
Section: Practical Barriersmentioning
confidence: 99%
“…In a recent study, Melendez-Calderon and colleagues suggest that SPARC should not be applied to linear velocities obtained from IMUs, and an alternative definition based on angular velocities may be of interest (Melendez-Calderon et al, 2021). However, techniques to correct drift due to strapdown integration (Woodman, 2007) were not employed in their study, as the authors suggest that it warrants a systematic analysis of the errors introduced in the smoothness estimate (Melendez-Calderon et al, 2021). Therefore, if the errors are accounted for, it should be possible to reliably measure SPARC using corrected linear velocities obtained from IMUs for a standardized pre-defined movement with a clear start and end posture.…”
Section: Practical Barriersmentioning
confidence: 99%
See 2 more Smart Citations